2018
DOI: 10.1073/pnas.1815031116
|View full text |Cite
|
Sign up to set email alerts
|

Dnase1l3deletion causes aberrations in length and end-motif frequencies in plasma DNA

Abstract: SignificanceCirculating DNA in plasma has many diagnostic applications, including noninvasive prenatal testing and cancer liquid biopsy. Plasma DNA consists of short fragments of DNA. However, there is little information about mechanisms that are involved in the fragmentation of plasma DNA. We showed that mice in which Dnase1l3 had been deleted showed aberrations in the fragmentation of plasma DNA. We also observed a change in the ranked frequencies of end motifs of plasma DNA caused by the Dnase1l3 deletion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
187
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 162 publications
(205 citation statements)
references
References 41 publications
15
187
3
Order By: Relevance
“…Furthermore, previous work using plasma DNA sequenced using the Pacific Bioscience Single Molecule, Real-Time (SMRT) system indicated that fragments in the 600 to 2,000 bp range accounted for less than 4.8% of the cf.DNA population. 9 Paired-end reads sharing the same start and end genomic coordinates were deemed PCR duplicates and were discarded from downstream analysis. Table S1 summarizes the number of nonduplicate fragments obtained for each condition.…”
Section: Dna Sequencing and Alignmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, previous work using plasma DNA sequenced using the Pacific Bioscience Single Molecule, Real-Time (SMRT) system indicated that fragments in the 600 to 2,000 bp range accounted for less than 4.8% of the cf.DNA population. 9 Paired-end reads sharing the same start and end genomic coordinates were deemed PCR duplicates and were discarded from downstream analysis. Table S1 summarizes the number of nonduplicate fragments obtained for each condition.…”
Section: Dna Sequencing and Alignmentmentioning
confidence: 99%
“…This clear preference for C-ends in all sizes of circulating cf.DNA fragments, as seen in Figure 3, suggests the presence of a nuclease that prefers to cleave 5 0 to a C. Previously, we had demonstrated that cf.DNA from WT mice had a high frequency of fragments ending in CCNN motifs (i.e., motifs consisting of two consecutive cytosines, followed by two nucleotides of any type) and that this preference for CCNN motifs in cf.DNA fragment ends was reduced in Dnase1l3-deficient mice. 9 Because C-end fragments are comprised of CCNN end motifs, we hypothesized that the nuclease responsible for the C-end preference might also be DNASE1L3.…”
Section: A-ends and G-ends Among Newly Released Cfdna Of Different Smentioning
confidence: 99%
See 1 more Smart Citation
“…eccDNA | cell-free DNA | noninvasive prenatal testing | plasma DNA topologics T he fragmentation patterns of cell-free DNA (cfDNA) in human plasma is an area of intense research interest (1)(2)(3)(4). Recent studies on the size distributions (1), end locations (5), and end motifs (3) revealed that these fragmentation patterns in cfDNA bore relationships with their tissues of origin.…”
mentioning
confidence: 99%
“…eccDNA | cell-free DNA | noninvasive prenatal testing | plasma DNA topologics T he fragmentation patterns of cell-free DNA (cfDNA) in human plasma is an area of intense research interest (1)(2)(3)(4). Recent studies on the size distributions (1), end locations (5), and end motifs (3) revealed that these fragmentation patterns in cfDNA bore relationships with their tissues of origin. In pregnancy, fetal-derived plasma DNA (mainly of placental origin) were observed to be linear fragments of DNA that were shorter than the maternal-derived (mainly of hematopoietic origin) DNA (1,5,6).…”
mentioning
confidence: 99%